SYSTEMATIC LITERATURE REVIEW (SLR) EVALUASI IMPLEMENTASI KURIKULUM MERDEKA PADA SEKOLAH MENENGAH KEJURUAN DALAM MENGHADAPI TANTANGAN INDUSTRI 4.0 - Kasili, Mukrin; Pramudibyo, Sugeng; Rahmandan, Hafid; A. Lahamutu, Mohamad Rizky; Aldio, Tesan; Yanino, Rafli M; Umar, Abdulrazik (Universitas Negeri Gorontalo, 2025)
This study aims to evaluate the implementation of the Merdeka Curriculum in Vocational High Schools (SMK) in responding to the challenges of the Industrial Revolution 4.0 through a Systematic Literature Review (SLR). A total of sixteen relevant sources published between 2020 and 2023 were analyzed to obtain a comprehensive understanding of teacher readiness, digital infrastructure, project-based learning (PjBL), and the alignment between schools and the industrial sector (DUDI). The findings show that although the Merdeka Curriculum is conceptually aligned with 21st-century competencies—particularly digital literacy, creativity, and problem solving—its implementation in SMKs remains constrained by limited teacher competence, inadequate technological facilities, and weak industrial partnerships. Project-Based Learning has been introduced but has not consistently resulted in authentic, industry-oriented projects. Furthermore, digital literacy among students and the digital readiness of schools are still at moderate levels, affecting the effectiveness of technology-based learning. The study concludes that strengthening teacher capacity, improving digital infrastructure, enhancing collaboration with industry, and ensuring deeper integration of PjBL are crucial for optimizing the implementation of the Merdeka Curriculum. These efforts are necessary to prepare vocational students to compete and adapt in the dynamic landscape of Industry 4.0.